2018
DOI: 10.1002/jper.17-0185
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of amixicile against Treponema denticola and other oral spirochetes associated with periodontal disease

Abstract: AMIX is effective in vitro in inhibiting growth and other processes central to virulence. AMIX could serve could serve as a new selective therapeutic tool for the treatment of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(113 reference statements)
1
7
0
1
Order By: Relevance
“…On the treatment side, could we preferentially target and block functional or metabolic pathways crucial to those taxa identified as differentially abundant in peri-implantitis or even at the earlier stage of peri-implant mucositis? Recent preliminary data in this direction indicate that growth, motility, and complement resistance in several oral Treponema species may be impaired by the administration of a specific oxidoreductase inhibitor (Reed et al 2018) or that administration of a C3 inhibitor of the alternative complement pathway attenuates the progression of periodontitis (Bostanci et al 2018). Despite the hypothetical nature of these open questions, we believe that a more finite understanding of peri-implant ecological pathways leading to the functional pathogenicity of the specialized peri-implant community is warranted and would ultimately prove beneficial for the long-term retention of dental implants.…”
Section: Concluding Comments and Perspectivesmentioning
confidence: 99%
“…On the treatment side, could we preferentially target and block functional or metabolic pathways crucial to those taxa identified as differentially abundant in peri-implantitis or even at the earlier stage of peri-implant mucositis? Recent preliminary data in this direction indicate that growth, motility, and complement resistance in several oral Treponema species may be impaired by the administration of a specific oxidoreductase inhibitor (Reed et al 2018) or that administration of a C3 inhibitor of the alternative complement pathway attenuates the progression of periodontitis (Bostanci et al 2018). Despite the hypothetical nature of these open questions, we believe that a more finite understanding of peri-implant ecological pathways leading to the functional pathogenicity of the specialized peri-implant community is warranted and would ultimately prove beneficial for the long-term retention of dental implants.…”
Section: Concluding Comments and Perspectivesmentioning
confidence: 99%
“…Previous studies reported a signi cant decrease post NSPT in Pg and Tf independent of the usage of placebo or AZM [13,18]. Contrarily, previous studies reported no intergroup differences in the prevalence of Pg, Tf [23,32] or Td [23,26,31,38]. Haffajee, et al [39] found a signi cant difference in the count of red-complex bacteria and some species of the orange complex for the group treated with azithromycin.…”
Section: Discussionmentioning
confidence: 93%
“…Some of these caused Lyme disease, leptospirosis, syphilis, and other human diseases. Moreover, Spirochaetes were closely related to periodontal disease and gingivitis (Reed et al, 2018 ; Yousefi et al, 2020 ; Zeng et al, 2021 ), and, in turn, periodontal disease impacted the risk of systemic diseases such as diabetes (Deng et al, 2018 ). Taken together, these changes occurring in the salivary microbiota of RTRs appeared to be associated with the new onset diabetes, periodontal disease, and gingivitis after renal transplant.…”
Section: Discussionmentioning
confidence: 99%